A personalized preoperative modeling system for internal fixation plates in long bone fracture surgery—A straightforward way from CT images to plate model. Issue 5 (4th September 2019) - Liu, Bin; Zhang, Song; Zhang, Jianxin; Xu, Zhao; Chen, Yanjie; Liu, Shujun; Qi, Wen; Yang, Liang
Abstract: Background: Long bone fractures are a type of physical damage with high incidence rates that have serious impacts on the normal lives of humans. Aims: How to obtain a preoperative internal fixation plate model before cutting muscle has become a critical issue. Materials and Methods: In this paper, we present a new personalized modeling system for internal fixation plates in long bone fracture surgery. This system can achieve straight semi‐automatic processing from CT images to 3D models. First, broken bones are separated in CT images. Second, the axes of long broken bones are extracted using 3D models. Third, the vertices on the broken bone cross‐sections are segmented. Fourth, rough alignment and fine registration are implemented. Results: An internal fixation plate is reconstructed for a long bone fracture. Discussion: Three validations indicate that this method framework is reasonable and feasible. Conclusion: This system can provide technical support for the personalized, minimally invasive and accurate operation on long bone fractures.